Bulbospinal nociceptive ON and OFF cells related neural circuits and transmitters - Peng, Bingxue; Jiao, Yingfu; Zhang, Yunchun; Li, Shian; Chen, Sihan; Xu, Saihong; Gao, Po; Fan, Yinghui; Yu, Weifeng (Frontiers in Pharmacology, 2023)
The rostral ventromedial medulla (RVM) is a bulbospinal nuclei in the descending pain modulation system, and directly affects spinal nociceptive transmission through pronociceptive ON cells and antinociceptive OFF cells in this area. The functional status of ON and OFF neurons play a pivotal role in pain chronification. As distinct pain modulative information converges in the RVM and affects ON and OFF cell excitability, neural circuits and transmitters correlated to RVM need to be defined for an in-depth understanding of central-mediated pain sensitivity. In this review, neural circuits including the role of the periaqueductal gray, locus coeruleus, parabrachial complex, hypothalamus, amygdala input to the RVM, and RVM output to the spinal dorsal horn are discussed. Meanwhile, the role of neurotransmitters is concluded, including serotonin, opioids, amino acids, cannabinoids, TRPV1, substance P and cholecystokinin, and their dynamic impact on both ON and OFF cell activities in modulating pain transmission. Via clarifying potential specific receptors of ON and OFF cells, more targeted therapies can be raised to generate pain relief for patients who suffer from chronic pain.